Class, Culture and Belonging in Rural Childhoods - Butler, Rose.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book explores how rural children negotiate economic insecurity and difference. Based on long-term ethnographic research in rural Australia, it shows that children draw on class-based ideas of moral worth, anchored in racialised and gendered understandings, to negotiate financial hardship and insecurity. Through close observations in the classroom, school yard and the home, and interviews with diverse young people, their parents and teachers, Class, Culture and Belonging in Rural Childhoods takes us deep into children's everyday struggles and their efforts to manage insecurity and belonging within a polarised economic landscape. This book offers compelling new analysis of children's experiences at a time of rapid and far-reaching change in rural communities and the world at large. This unique and engaging ethnography of rural Australia makes an important and timely contribution to wider understandings of how children navigate the precarious circumstances of the present.
Introduction -- Chapter 1. Children in an Insecure Economy -- Chapter 2. Economy, Identity and Fairness -- Chapter 3. Researching Childhoods -- Chapter 4. Going without: dignity and resentment -- Chapter 5. Staying within: politics of difference -- Chapter 6. Cutting down: entitlement and solidarity -- Chapter 7: Stigma and boundary work -- Conclusion.
Keywords: Sociology; Family policy; Ethnology; Community development; Social service; Welfare state; Sociology; Children, Youth and Family Policy; Sociocultural Anthropology; Social Work and Community Development; Welfare